O estudo das estruturas adjetivas numa perspectiva textual discursiva. - Morais, Carlene de Souza (2009)
The present work interferes in the theory partner-interacionista and it has for objective to analyze in a textual-discursive perspective, the adjectival structures in different textual goods. The protected hypothesis is the that the activities proposed in text books of Portuguese language of the Fundamental Teaching they don't take the student to notice the different functions and the sense effects that those structures produce in the text. To prove it, they are taken as objects of analysis three selected goods of the text books of Portuguese language: a debate; an interview and a report. The proposed reflection, seeking it a change in the work with the Portuguese language is based in the conception language bakhtiniana, which postulates that the true substance of the language is constituted by the social phenomenon of the interaction. In that sense, it can be thought about a study of the language guided in another direction, in that it is not privileged the identification and the classification of the linguistic categories in sentences descontextualizadas, but the observation of the use of those categories in the texts. For so much, it comes a study of the adjectival structures, observing your operation and the sense effects produced by those structures in the texts, in way to enlarge the student's discursive competence, turning him proficient in the use of the oral language and writing.